Le Congo et l’huile de palme. Un siècle. Un cycle ? - Henri Nicolaï (Belgeo)
Palm oil has been a major symbol of colonial Congo as produced by European companies from the fruit picked by African villagers, mostly in natural palm groves. Traditional food for the Congolese population, palm oil only became a major export product when Lever, the British soap maker, was assigned large concessions in the centre of the country in 1911. Later, a large number of smaller companies, Belgian or Portuguese, gained a monopoly on the purchase of fruit in palm oil areas. Factories, social, medical, school facilities and transport networks started to structure some territories, sometimes leading to a true regional construction, as in the Kwilu district.Yet the system presented a dark side: popular reaction movements (as the Pende revolt in 1931) resulting from constraints in recruitment; land litigation due to the assignment of vast concessions; exclusion of Africans from the management; freezing of evolution in village agriculture. Although the Congo had become the first African exporter of palm oil and the second at world scale in the 1950s, the system failed to induce a true development process.The second part of the paper examines the deterioration of the system with decolonization: abandonment of most of the oil palm mills and large plantations; departure of big companies partially recovered by local contractors; deconstruction of structures and facilities. Oil export ceased at the end of the last century. Nowadays the industrial production can no longer ensure the supply of soap factories but an artisanal system of palm oil extraction in villages covers most of the urban needs.The third part is devoted to future prospects: improvement of artisanal production; possible revival of agro-industrial production favoured by a growth in world demand; arrival of new investors (notably from Asia) and emergence of new uses - notably as biofuel- but the destruction of forests and land monopolization by foreign companies are a matter of concern.